Institutional Determinants of Sharia Consumers’ Motivation in Indonesia - Muhajir, Muhammad Nur Alam; Erwin, Erwin; Alisiya, Dima Ade; Samsul, Samsul; Rasmi, Rasmi (MEC-J (Management and Economics Journal), 2025)
This research is important because several behavioral and psychological factors such as religiosity, Islamic business ethics, trust, satisfaction, and perception are frequently reported to influence the motivation of sharia  consumers.  This study aims to analyze the influence of religiosity, Islamic business ethics, trust, satisfaction and perception on the motivation of sharia consumers in Indonesia. Data were analyzed using the Structural Equation Model Partial Least Square (SEM PLS) method. This study was conducted with a quantitative approach and data collection techniques through Accidental Sampling, with a sample size of 110 respondents obtained through questionnaires. Data were analyzed using the Structural Equation Model Partial Least Square (SEM PLS) method. The population in this study were sharia consumers in Indonesia.Based on the empirical findings, this study contributes theoretically by clarifying the roles and interactions of religiosity, Islamic business ethics, trust, satisfaction, and perception in shaping sharia consumer motivation. The results also present practical implications for sharia business actors and policy makers in designing strategies that strengthen and sustain sharia consumer motivation. The novelty of this study lies in its analytical shift from prior research that primarily emphasized sharia consumer purchasing behavior, toward a deeper examination of consumer motivation. Furthermore, this study extends the discussion of boycott-related motivations by integrating non-economic variables such as religiosity, Islamic business ethics, trust, satisfaction, and perception.